Determinants of the duration of tax litigation an empirical study of the Philippine Court of Tax Appeals civil en banc cases from 2004 to 2016 - Licos, Fritz Kyle P. (School of Economics, University of the Philippines Diliman, 2018)
This paper analyzes the determinants of the duration of tax litigation in the Philippine Court of Tax Appeals en banc by analyzing an original dataset of 1,336 civil cases. This study focuses mainly of case-level determinants. Using proportional hazard regression models, results show that the commissioning of an independent CPA in the appealed case, also known as the use of expert assessments, is found to be a significant factor affecting case duration. In addition to this case-level factor, this paper finds that the court's organizational expansion in 2010 did not exhibit any significant effect in the disposition time of cases.